UMPSA leads AEROGROUND research to develop Autonomous Aero-Ground System for national resilience - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 6 October 2025 – Director of the Centre for Innovation and Technology Transfer and Principal Research Fellow at the Advanced Industrial Technology Centre, Associate Professor Ts. Dr. Muhammad Aizzat Zakaria from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), successfully secured the 2025 Long-Term Research Grant Scheme (LRGS) from the Ministry of Higher Education (MOHE) worth RM1.4 million to lead a high-impact research project entitled ‘AEROGROUND: Investigation of Autonomous Aero-Ground Robot for Surveillance and Reconnaissance – Artificial Intelligence Driven Navigation with Secure Edge Computing Integration’.